Grumpy monkey : too many bugs - Lang, Suzanne; Lang, Max, 1982- (New York : Random House, 2024)
"When Norman shows Jim his pet butterfly, Butterfly-Butterfly, Jim is suitably impressed, especially when Norman spouts butterfly facts. Then Norman adds Beetle-Beetle 1 and Beetle-Beetle 2 and so many more to his menagerie. Now Norman spends all his time feeding and caring for his pets and doesn t have time to play. Grumpy Monkey Jim feels left out. And when all the bugs have babies, Jim declares that Norman has too many and persuades his friend to set them free. But then Norman sees a ladybug "--
Ages 4-6.
Keywords: Butterflies as pets -- Juvenile fiction; Insects -- Juvenile fiction; Chimpanzees -- Juvenile fiction; Animals -- Juvenile fiction; Readers (Publications); Animal fiction